2006
DOI: 10.1002/cne.21128
|View full text |Cite
|
Sign up to set email alerts
|

Origins and migratory routes of murine Cajal‐Retzius cells

Abstract: The first layer that appears in the cortical neuroepithelium, the preplate, forms in the upper part of the cortex immediately below the pial surface. In mice, this layer exists between embryonic days (E) 10 and 13, and it hosts different cell populations. Here, we have studied the first cell population generated in the preplate, the Cajal‐Retzius cells. There is considerable confusion regarding these cells with respect to both their site of generation and the migratory routes that they follow. This perhaps is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 52 publications
4
70
1
Order By: Relevance
“…Consistently, fate mapping and cell lineage tracing studies have shown that CR cells arise from specific locations along the rostrocaudal and dorsoventral axes of the pallial VZ (Bielle et al, 2005;GarciaMoreno et al, 2007;Imayoshi et al, 2008;Monuki et al, 2001;Takiguchi-Hayashi et al, 2004;Yoshida et al, 2006;Zhao et al, 2006). Four different sites of CR generation have been identified, comprising the pallial domain of the septum in the rostromedial (RM) pallium (Bielle et al, 2005), the ventral pallium (VP) laterally (Bielle et al, 2005), the prospective choroid plexus, and the cortical hem (CH) caudally (Garcia-Moreno et al, 2007;Imayoshi et al, 2008;Monuki et al, 2001;Takiguchi-Hayashi et al, 2004;Yoshida et al, 2006;Zhao et al, 2006). CR cells migrate tangentially from these focal sites to populate the entire cortical surface.…”
Section: Introductionmentioning
confidence: 87%
“…Consistently, fate mapping and cell lineage tracing studies have shown that CR cells arise from specific locations along the rostrocaudal and dorsoventral axes of the pallial VZ (Bielle et al, 2005;GarciaMoreno et al, 2007;Imayoshi et al, 2008;Monuki et al, 2001;Takiguchi-Hayashi et al, 2004;Yoshida et al, 2006;Zhao et al, 2006). Four different sites of CR generation have been identified, comprising the pallial domain of the septum in the rostromedial (RM) pallium (Bielle et al, 2005), the ventral pallium (VP) laterally (Bielle et al, 2005), the prospective choroid plexus, and the cortical hem (CH) caudally (Garcia-Moreno et al, 2007;Imayoshi et al, 2008;Monuki et al, 2001;Takiguchi-Hayashi et al, 2004;Yoshida et al, 2006;Zhao et al, 2006). CR cells migrate tangentially from these focal sites to populate the entire cortical surface.…”
Section: Introductionmentioning
confidence: 87%
“…However, extrapolation of findings from in vitro assays to the behavior of progenitors in the living brain should be taken with caution. For example, early cortical progenitors cultured in vitro first generate Cajal-Retzius cells, although in the living animal these neurons are generated from other progenitors, outside the dorsal pallium (54,55).…”
Section: Emx2 Progenitors Support Both the Restricted And The Sequentialmentioning
confidence: 99%
“…One of the main populations of MZ is CR neurons, the first-born neurons that invade tangentially into MZ from the extra-cortical origins (Garcia-Moreno et al, 2007 Cresyl violet staining of the E18.5 dorsal pallium (A-C). In situ hybridization on parasagittal sections of the E18.5 dorsal pallium with Wnt7b (D-F) and Tbr1 probes (G-I).…”
Section: Shh Immunoreactivity Is Weakly Detected In Both the Prolifermentioning
confidence: 99%